Testing of a reusable chemical warming pad and an insulating jacket to manage hypothermia of preterm or low birthweight neonates - Anisuddin Ahmed; Fariya Rahman; Md. Mahinur Islam; Mohammad Hridoy Patwary; K. M. Tanvir; Saifuddin Ahmed; Abul Hussam; Md. Mominul Islam; Mats Målqvist; Ahmed Ehsanur Rahman; Shams El Arifeen; Syed Moshfiqur Rahman (Scientific Reports)
Abstract Hypothermia remains a leading contributing factor to neonatal mortality. This study reports testing of a thermoregulatory device—‘Thermal Jacket’ that includes a reusable chemical warming pad (CWP) and an insulating jacket designed for hypothermia management. The laboratory experiments were conducted in two distinct phases between February’21 and June’22. In phase 1, a ternary composite of Sodium-Acetate-Trihydrate, Glycerol, Paraffin, and water contained in a high-density polyethylene-pouch named ‘CWP’ was finalised, and an insulating jacket was designed for targeted heat retention. In phase 2, the device’s efficacy was evaluated using a mannequin in a controlled setting. The sample size was 81 events. Welch’s t-test, ANOVA, and GEE were used to assess any significant differences between successful and failed events. Among 81 events, approximately 93% events of CWP and 98% events of insulating jacket successfully maintained temperature within 36–38°C for 120 minutes. Moreover, ambient temperature, reuse of CWPs, humidity did not have any significant effect on the success rate of the CWP and insulating jacket. Thermal Jacket had achieved and sustained the temperature range of 36–38°C for 2 hours. While this study used mannequin, clinical trial with preterm or low birthweight neonates is imperative to assess its effectiveness for thermal care management.